1241Alcohol and hypertensive disorders of pregnancy: a negative control analysis. (2nd September 2021) - Martin, Flo; Fraser, Abigail; Zuccolo, Luisa
Abstract: Background: Alcohol increases blood pressure, yet estimates of its association with pre-eclampsia range from positive to negative. Here we estimated the association of maternal drinking during pregnancy with preeclampsia and gestational hypertension, separately and jointly as hypertensive disorders of pregnancy (HDP). We also used partner's alcohol intake as a negative control exposure to strengthen causal inference. Methods: We used data on self-reported alcohol intake in the Avon Longitudinal Study of Parents And Children (ALSPAC, N∼9, 000). HDP was ascertained from obstetric notes. Multivariable multinomial regression models were adjusted for confounders and mutually-adjusted for partner's or maternal alcohol. Sensitivity analyses assessed the robustness of results to assumptions of no selection bias, no reporting bias, and no residual confounding (e.g. comparing estimates for beer and wine separately, which have different socioeconomic patterning). Results: In mutually-adjusted analyses, maternal and partner's drinking were associated with decreased HDP odds (OR(95% CI): 0.86(0.77–0.96) and 0.82(0.70-0.97)) respectively. In contrast, the negative control design confirmed the expected associations for maternal but not partner's smoking (figure), demonstrating the validity of this approach. Multiple sensitivity analyses did not alter results. Estimates were more extreme for increasing levels of wine compared to increasing levels of beer drinking. Conclusions: Our extensive negative control and sensitivity analyses point at confounding mechanisms shared between mothers and partners as the most plausible explanation for the alcohol-HDP association. Key messages: It is unlikely that alcohol intake in pregnancy reduces the risk of HDP.